Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 5 - Polynomials and Factoring - 5.7 Solving Quadratic Equations by Factoring - 5.7 Exercise Set - Page 351: 24


$x=\left\{ -2,9 \right\}$

Work Step by Step

Factoring the given equation, $ x^2-7x-18=0 ,$ results to \begin{array}{l}\require{cancel} (x-9)(x+2)=0 .\end{array} Equating each factor to zero (Zero Product Principle), then the solutions to the equation, $ (x-9)(x+2)=0 ,$ is \begin{array}{l}\require{cancel} x-9=0 \\\\ x=9 ,\\\\\text{OR}\\\\ x+2=0 \\\\ x=-2 .\end{array} Hence, $ x=\left\{ -2,9 \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.